HUBUNGAN LINTAS SELAT TAIWAN DAN TIONGKOK TERKAIT KETERGANTUNGAN DAGANG PADA PEMERINTAHAN TSAI ING-WEN - Suwandy, Dhanico; Simanjuntak, Triesanto Romulo; Seba, Roberto Octavianus Cornelis (Department of International Relations Universitas Satya Negara Indonesia, 2023)
Taiwan and China are two countries that have a long history of ideology, government, and territory. The two countries have been at war since 1920 between the Chinese Communist Party and the Kuomintang until the ROC government finally moved to the island of Taiwan. Since then, cross-strait relations politically have not been good. On the other hand, trade between the two countries is very good, especially after the formation of the ECFA trade agreement in 2010 which made exports and imports easier. In trade expectations theory, this research analyzes the existence of a “peaceful trade” relationship between the two countries through trade and investment. China has trade dependence on Taiwan in integrated circuit commodities because Taiwan can produce good quality integrated circuits. Based on the principle of dependency, trade relations create “peaceful trade” conditions for cross-strait relations in unstable political conditions. Integrated circuits are also needed by many countries so that Taiwan can control 60% of trade in the global market. Taiwan also has dependence on China for FDI. The value of Taiwan’s FDI to China in 2021 is 46 times higher than integrated circuit exports to China in 2021. This research looks at cross-strait relations between Taiwan and China in ECFA cooperation regarding cross-border trade during the Tsai Ing-wen administration. The qualitative method used in this research took data from the Ministry of Finance of Taiwan. This research analyzes the trade relations between the two countries from exports, imports and FDI as the main findings so that the dependence of the economies of the two countries to date has created conditions for cross-strait relations.